Study of Fatigue Fractography of Mild Steel Used in Automotive Industry - Zainulabdeen, Ahmed Ameed (Al-Khwarizmi Engineering Journal, 2019)
Fatigue failure is almost considered as the predominant problem affecting automotive parts under dynamic loading condition. Thus, more understanding of crack behavior during fatigue can strongly help in finding the proper mechanism to avoid the final fracture and extent the service life of components. The main goal of this paper is to study the fracture behavior of low carbon steel which is used mostly in automotive industry. For this purpose, the fractography of samples subjected to high and low stress levels in fatigue test then was evaluated and analyzed. Hardness and tensile tests were carried out to determine the properties of used steel. Also, the samples were characterized by microstructure test and XRD analysis to examine the constitute phases. The fatigue test (S-N curve) was done at stress ratio (R= -1), and the fracture examination was perform using Scanning Electron Microscope (SEM). The results of microstructure and XRD analysis were indicating that the Ferrite and a little amount of pearlite are the dominant phases of this steel. Whereas, the fractography observations reveal that the void coalescence ductile fracture is the main failure mode in samples with high stress level, while the ductile fracture (void coalescence) with Transgranular Cleavage fracture was noticed in low stress fatigue mode for this alloy.